Myf5 and Myogenin in the development of thymic myoid cells: implications for a murine in vivo model of myasthenia gravis - Hu, Bo; Simon-Keller, Katja; Marx, Alexander; Porubský, Štefan (Experimental neurology, 2016)
Myasthenia gravis (MG) is caused by autoantibodies against the neuromuscular junction of striated muscle. Most MG patients have autoreactive T- and B-cells directed to the acetylcholine receptor (AChR). To achieve immunologic tolerance, developing thymocytes are normally eliminated after recognition of self-antigen-derived peptides. Presentation of muscle-specific antigens is likely achieved through two pathways: on medullary thymic epithelial cells and on medullary dendritic cells cross-presenting peptides derived from a unique population of thymic myoid cells (TMC). Decades ago, it has been hypothesized that TMC play a key role in the induction of immunological tolerance towards skeletal muscle antigens. However, an experimental model to address this postulate has not been available. To generate such a model, we tested the hypothesis that the development of TMC depends on myogenic regulatory factors. To this end, we utilized Myf5-deficient mice, which lack the first wave of muscle cells but form normal skeletal muscles later during development, and Myogenin-deficient mice, which fail to form differentiated myofibers. We demonstrate for the first time that Myf5- and Myogenin-deficient mice showed a partial or complete, respectively, loss of TMC in an otherwise regularly structured thymus. To overcome early postnatal lethality of muscle-deficient, Myogenin-knockout mice we transplanted Myogenin-deficient fetal thymuses into Foxn1nu/nu mice that lack their own thymus anlage. We found that the transplants are functional but lack TMC. In combination with established immunization strategies (utilizing AChR or Titin), this model should enable us in the future testing the hypothesis that TMC play an indispensable role in the development of central tolerance towards striated muscle antigens.